Studies of EPR parameters for Mn5+-doped Ca2(MO4)Cl (M = P, As, V) crystals from a two-mechanism model. Issue 3 (12th December 2014) - Wu, Xiao-Xuan; Yu, Xin-Peng; Zheng, Wen-Chen
Abstract : The EPR parameters (zero-field splitting D and g -factors g //, g ⊥ ) of Mn 5+ -doped solid state laser materials Ca2 (MO4 )Cl (M = P, As, V) are calculated from the complete high-order perturbation formulas of EPR parameters based on the two-mechanism model for 3 d 2 ions in a approximately tetragonal tetrahedron. The model includes the contributions from both the crystal-field (CF) mechanism and the charge-transfer (CT) mechanism (the latter is neglected in crystal field theory). The calculated results suggest that the contribution to EPR parameters due to CT mechanism is important. So, in the cases of high valence state 3 d n ions in crystals, the reasonable explanation of EPR parameters should take both CF and CT mechanisms into account.